Screening of electrocoagulation process parameters for treated palm oil mill effluent using minimum-runs resolution IV design - Mujeli, Mustapha; Hussain, S. A.; Ismail, M. H. S.; Awang Biak, Dayang Radiah; Jami, Mohammed Saedi (Springer Berlin Heidelberg, 2019)
The present study aimed at the screening of parameters for electrocoagulation treatment of treated palm oil mill efuent using minimum-runs resolution IV design. The responses examined include: chemical oxygen demand removal (%), total suspended solids removal (%) and turbidity reduction (%), and the varied dependent factors comprise: electrical current density (mA/cm2), time (min), pH, electrolyte concentration (g/L), stirring speed (rpm), electrode spacing (mm) and electrode confguration (monopolar or dipolar). The statistical results revealed that the current density has a signifcant infuence on the treatment performance at two-level interactions with pH, electrode spacing and electrode concentration and at three-level correlations with time and pH. Thus, the most important factors afecting the removal efciency of the organic compounds were found to be pH, time, electrode spacing, electrolyte concentration and electrode confguration at a P value less than 0.05, respectively, in the descending order of signifcance. Therefore, the optimized electrocoagulation process could be reached with current density equal to 5 mA/cm2, electrolysis time of 5 min, electrode spacing of 5 mm and using monopolar electrode confguration. This combination provided the maximum ability of the process for chemical oxygen demand (68.84%), total suspended solids (93.27%) and turbidity reduction (92.88%) predictions, with the corresponding experimental values of 69.27, 97.59 and 96.91%, respectively.